TO THE PROBLEM OF STUDYING THE VISUAL PERCEPTION OF STUDENTS WITH LOW VISION WITHIN (Education in the 21st Century, 2022)
The article analyzes the results of the studies on the formation and development of visual perception of visually impaired children in the aspect of correction and prevention of optical- graphic writing disorders, conducted by foreign and domestic authors. First of all, the importance of the problem is determined by the fact that the visual impairment makes the process of reading and writing of these children much more difficult. Owing to the insufficient development of visual perception, visually impaired students write letters, syllables or words together or excessively apart, dislocate the writing straightness etc.